Economic Growth and Poverty in West Kalimantan: Economic Growth and Poverty in West Kalimantan - Hendra Eka Wahyudianto (Jurnal Forum Analisis Statistik, 2021)
Ideally, the economic development that has been carried out will produce high economic growth as well as improve the welfare of the community. However, based on existing realities, the benefits of economic growth cannot be felt directly, resulting in poverty. In an effort to analyze economic growth and poverty, this study was performed by collecting samples of all districts/cities in West Kalimantan Province from 2010 to 2020, which were then analyzed using two-stages simultaneous equations. The endogenous variables in this study were economic growth and poverty, while the exogenous variables were household consumption, investments, per capita income, and agriculture sector growth. The results showed that poverty had a negative impact on economic growth, but household consumption and investment had no effect. At the same time, per capita income economic growth has a negative effect on poverty, while economic growth and agriculture sector growth has no effects on poverty. Therefore, the quality of economic growth in West Kalimantan must be further improved by focusing on the poor (pro poor).